Las capacidades físicas condicionales y su incidencia en el desarrollo de los fundamentos técnicos del arquero de fútbol en las divisiones formativas del club Liga Deportiva Universitaria de Loja durante el primer quimestre del campeonato ecuatoriano de fútbol 2014 - Espinosa Valencia, Jover Orlando (2015)
Football is one of the most practiced worldwide, both popular and professional sports, football history, far from being always linked to the greatness of a popular sport, has been subject to the vicissitudes of history and adapting to each culture up to become what we know today as football, the subject of this research is "The Conditional Physical Abilities and its impact on the development of the technical fundamentals of football goalkeeper in training divisions of Liga Deportiva club University of Loja in the first quimestre the Ecuadorian Football Championship "From this the issues raised in this research is manifested in how the work of conditional physical abilities affect the improvement of the technical fundamentals of soccer goalkeepers, your goal generally focuses on determining the incidence the conditional physical skills in improving the technical fundamentals of soccer goalkeepers formative divisions of Club LDU Loja, using a methodology of qualitative nature, diagnosis through the implementation of the survey of archers in training and coaching 100% believe that the work of the conditional physical abilities by improving the technical preparation of archers from this apply and evaluate the proposed work through resulting in the improvement of conditional physical abilities test in the following percentages: 88% abdominal strength, speed 67%, 72% arm strength, endurance and flexibility 24% 64%, concluding that a good job of physical abilities Conditional direct impact on technical grounds on archers allowing better performance in the Ecuadorian soccer championship. .